A Hierarchy of Harm: A Meta-analysis of Infection, Thrombosis, and Mortality Risks Across Central Catheters, Arteriovenous Grafts, and Fistulas - Anak Agung Ngurah Gede Anggra Pramana; Anthony Wijaya; Putu Chandra Wibawa; I Gusti Agung Bagus Krisna Wibawa (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Vascular access is a critical lifeline for patients with end-stage kidney disease requiring hemodialysis. The optimal choice among central venous catheters (CVCs), arteriovenous grafts (AVGs), and arteriovenous fistulas (AVFs) is a subject of intense debate, as each modality carries a distinct profile of risks. This meta-analysis was performed to establish a definitive, quantitative hierarchy of these risks to better inform clinical and policy decisions. Methods: A systematic search of PubMed, Scopus, and the Cochrane Library was conducted for studies published between January 2015 and September 2025 that compared complication rates among CVCs, AVGs, and AVFs in adult hemodialysis patients. Seven high-quality cohort studies met the inclusion criteria, encompassing 18,542 patients. Data on access-related bloodstream infections (ARBSI), access circuit thrombosis/dysfunction, and all-cause mortality were extracted. Pairwise meta-analyses using a random-effects model calculated pooled risk ratios (RR) and 95% confidence intervals (CI). Results: Central venous catheters were associated with a profoundly higher risk of ARBSI compared to both AVFs (RR 8.12, 95% CI 6.98–9.45, p < 0.001) and AVGs (RR 4.55, 95% CI 3.89–5.33, p < 0.001). Arteriovenous grafts demonstrated a markedly higher risk of access circuit thrombosis compared to AVFs (RR 2.78, 95% CI 2.41–3.21, p < 0.001). All-cause mortality was highest in patients with CVCs, showing a significantly increased risk compared to AVF users (RR 1.92, 95% CI 1.68–2.19, p < 0.001). Conclusion: This meta-analysis provides robust, contemporary quantitative evidence for a clear hierarchy of harm in hemodialysis access. CVCs pose the greatest risk for infection and mortality, AVGs present the highest risk for thrombosis, and AVFs represent the safest option. These data provide a powerful rationale for reinforcing systemic healthcare initiatives aimed at minimizing CVC exposure and promoting timely AVF placement.